2016
DOI: 10.1128/aac.01486-16
|View full text |Cite|
|
Sign up to set email alerts
|

Acquisition of mcr-1 Plasmid-Mediated Colistin Resistance in Escherichia coli and Klebsiella pneumoniae during Hajj 2013 and 2014

Abstract: bA plasmid-mediated transferable colistin resistance gene, mcr-1, was recently described in China (1) and was rapidly reported in several other countries (2). The spread of the mcr-1 gene was not only reported in Escherichia coli but also associated with other Enterobacteriaceae species isolated from human clinical samples, farm animals, and travelers (2, 3). However, whether or not the mcr-1 gene is acquired during the Hajj (the Muslim pilgrimage to Mecca) remains unknown.We conducted two cohort studies of pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 11 publications
1
34
0
Order By: Relevance
“…Two French pilgrims carried S. enterica, resistant to ceftriaxone, gentamycin, and colistin after the 2013 Hajj [62]. Mrc-1 resistance gene screening from rectal swabs was conducted in French pilgrims in 2013-2014 and found an acquisition rate of 9.0% after Hajj [63].…”
Section: Hajj and Antimicrobial-resistant Bacteriamentioning
confidence: 99%
“…Two French pilgrims carried S. enterica, resistant to ceftriaxone, gentamycin, and colistin after the 2013 Hajj [62]. Mrc-1 resistance gene screening from rectal swabs was conducted in French pilgrims in 2013-2014 and found an acquisition rate of 9.0% after Hajj [63].…”
Section: Hajj and Antimicrobial-resistant Bacteriamentioning
confidence: 99%
“…55 The identification of mcr-1mediated colistin resistance in E. coli and Klebsiella pneumoniae in pilgrims attending the annual Hajj indicates a risk for acquisition in those attending mass gatherings. 60 The initial description of mcr-1 was in 21% of healthy swine at slaughter, 15% of marketed pork and chicken meat, and 1% of hospitalized patients in China. 20 The first human isolate was detected in E. coli in Latin America.…”
Section: Plasmid-mediated Colistin Resistancementioning
confidence: 99%
“…Recently studies on returning French pilgrims have shown that participation in the Hajj increases carriage rates of enteric pathogens including Tropheryma whipplei [4], multidrug-resistant nontyphoidal Salmonella [5], CTX-M type extended-spectrum β-lactamase producing E. coli and Klebsiella pneumoniae [6], colistin-resistant E. coli and K. pneumoniae and carbapenemase-producing E. coli [7,8]. Moreover, acquisition of CTX-M genes at the Hajj was associated with the occurrence of diarrhea and use of β-lactams [9].…”
Section: Introductionmentioning
confidence: 99%